Optical, anticancer, photoluminescent, and electrochemical properties of crystalline ZnS quantum dots. Issue 3 (10th January 2022) - Assadullah, Insaaf; Bhat, Aadil Ahmad; Malik, Javied Hamid; Malik, Khurshaid Ahmad; Tomar, Radha
Abstract: In this study, we report the fabrication of binary chalcogenide zinc sulfide (ZnS) quantum dots (QDs) paying a facial, economical, eco‐friendly, and template‐free chemical method. The as‐synthesized nanomaterial has a single cubic phase; based on its structural features, it was confirmed that the nanoparticles are grown as QDs (2‐10 nm). Morphological studies display the formation of agglomerated QDs (3 nm). The energy‐dispersive spectroscopy shows that the essential elements are in the stoichiometric ratio as in the precursor solutions. Optical properties confirmed that the QDs are suitable for optoelectronic devices revealing room‐temperature photoluminescence. The charge‐storage electrochemical activity was explored via electrochemical characterization performances. Electrochemical studies show that the synthesized material has charge storage ability. And according to the International Commission on Illumination, the ZnS QDs show green emission, thus presenting that the material will be useful for biological applications. In addition, these nanoparticles exhibit incredible anticancer activities especially against breast cancer cells and may be used for biological or biomedical applications as well.